Distributional Effects of Macroeconomic Policy Choices in Emerging Market Economies - Eswar Prasad (Institute for the Study of Labor (IZA), 2013)
Distributional consequences typically receive limited attention in economic models that analyze the effects of monetary and financial sector policies. These consequences deserve more attention since financial markets are incomplete, imperfect, and economic agents' access to them is often limited. This limits households' ability to insure against household-specific (or sector-specific) shocks and magnifies the distributional effects of aggregate macroeconomic fluctuations and associated policy responses. These effects are likely to be even larger in emerging market and low-income economies beset by financial frictions. The political economy surrounding distributional consequences can sometimes lead to policy measures that reduce aggregate welfare. I argue that it is important to take better account of distributional rather than just aggregate consequences when evaluating specific policy interventions as well as the mix of different policies.
Keywords: E5; E6; F4; 330; income and wealth distribution; inequality; emerging markets; financial frictions; monetary policy; macroeconomic policies; Geldpolitik; Finanzmarktregulierung; Wechselkurspolitik; Verteilungswirkung; Schwellenländer; Entwicklungsländer